Pengaruh Motivasi Kerja Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior (OCB) Karyawan CU Betang Asi Kantor Pusat Palangka Raya - Monika, Vida Aknes; Anggen, Yohanes Kalvin; Harinie, Luluk Tri (Jurnal Manajemen Sains dan Organisasi, 2021)
Purpose - This study aims to determine how much influence Work Motivation and Organizational Commitment have on Organizational Citizenship Behavior (OCB) of Betang Asi CU employees at Palangka Raya Head Office. Design/Methodology/Approach - The research method uses a quantitative descriptive approach with a sample of 34 respondents. The analytical techniques in this study include descriptive analysis and Structural Equation Model (SEM) with the Smart-PLS analysis tool. Finding - The results of the Smart-PLS analysis show that work motivation has a positive and significant effect on organizational citizenship behavior, organizational commitment has a positive and significant effect on organizational citizenship behavior.